Implementation of Industrial Based Islamic Education Management in Pesantren Darussalam Al-Fatah Cilacap - Guntur Dwi Purwanto; Mohammad Ulyan; Abdul Basit (BIRCU, 2021)
Educational management is an important reference in the management of industrial-based Islamic boarding schools. When the management of a leader must go through several things, including planning, organizing, and planning industry-based learning. This research includes a qualitative descriptive approach to da'wah management. The data source used in this research is a literature review. Collecting data in this study using observation, interviews, and documentation. Islamic boarding school Darussalam Al-Fatah Cilacap is an industry-based Islamic boarding school. This was done to follow developments in the industrial revolution 4.0. Therefore, researchers feel it is important for the management of Islamic education at the Darussalam Al-Fatah Islamic boarding school in Cilacap. The results of the application of Islamic education management include, a) soroggan, with the bin-nazhr method, the tahfidz method, the talaqqi method, and the tikrar method, b) taddabur, c) habituation of the Hasbanah and Isyraq prayers, d) rewards for students, e ) the application of industrial learning, and f) the benefits of evaluating industry-based learning at the Darussalam Al-Fatah Cilacap Islamic boarding school.